Improving Children's Numeracy Skills Using Number Sticks in Group B at Baiturrahman Islamic Kindergarten Tanjung - Musafir; Hadiyaturrido; Muh. Hamdani (Pustaka Edukasi: Jurnal Pendidikan Indonesia, 2025)
The purpose of this study was to improve numeracy skills through the use of number sticks in group B of the Baiturrahman Tanjung Islamic Kindergarten in the 2023/204 academic year for 15 children aged 5-6 years, consisting of 5 boys and 10 girls. The research method used was classroom action research (CAR), which was carried out and completed in two learning cycles. The data collection instruments used in this study were teacher activity observation sheets, child arithmetic activity observation sheets with 7 indicators, and child arithmetic skill development assessment sheets. The results of this study indicate that the arithmetic skills of children in Group B at Baiturrahman Tanjung Islamic Kindergarten improved with the use of number sticks. This was evident in the children's classical mastery scores in the pre-cycle, which were only 20%. After cycle I, the scores reached 46.6%, with 1 child achieving the BSB criterion, 6 children achieving the BSH criterion, and 8 other children not yet mastering the BB and MB criteria. Meanwhile, in cycle II, the children's classical mastery increased to 86.6%, with 7 children achieving the BSB criterion, 6 children achieving the BSH criterion, and the remaining 13.3% or 2 children achieving the MB criterion. Thus, of the 15 children in group B, 86.6% had achieved the Maximum Completion Criteria (KKM) set. In this study, it can be said that 80% of the predetermined success rate had been achieved. Keywords: numeracy skills, number sticks, classroom action research, early childhood education